Clinical, diagnostic and treatment of mental disorders as a component of epilepsy - Aliyev NA; Aliyev ZN (Global Journal of Rare Diseases - Peertechz Publications, 2019)
It is well known that ILAE (International League Against Epilepsy) has prepared an offi cial report on "practical clinical determination of epilepsy" [1]. In this report, ILAE aims to broaden the understanding of epilepsy according tepileptologist's perceptions of epilepsy. This includes the time frame for determining the clinical status and diagnosis described below.